Peningkatan Pengetahuan tentang Penanganan Pasien COVID-19 dengan Komorbid pada Ibu Rumah Tangga - Maulida, Iroma; Umriaty, Umriaty; Arisanty, Novia Ludha; Rahmanindar, Nora; Leny, Leny (Shihatuna : Jurnal Pengabdian Kesehatan Masyarakat, 2023)
Covid-19 is a dangerous infectious disease because the increase in the number of cases takes place quite quickly, and spreads to various countries in a short time. Patients with comorbid diseases are one of the groups that are vulnerable to being infected with the Corona-19 virus. If infected with the Corona virus, the comorbid group has a higher risk of experiencing severe COVID-19 symptoms and requires intensive care, and even has a higher risk of dying. Through an interview with the chairman of Dawis1, it was discovered that not a few members did not want to vaccinate against Covid-19 because they suffered from other diseases such as hypertension or shortness of breath. For this reason, this service activity aims to increase the knowledge of housewives as part of the family about COVID-19 disease and the care of comorbid Covid patients and Covid-19 vaccinations for comorbid sufferers. The method used is counseling which is carried out to the women of the Dawis 1 group RT.06 RW.01 Kejambon Village, East Tegal District, Central Java, located in one of the houses of the Dasa Wisma members. The results of the service activities were the implementation of counseling on November 21, 2021 by 3 resource persons and attended by 16 housewives as well as increasing knowledge of mothers about Covid-19 disease, covid-19 vaccination and family support/handling for Covid-19 sufferers with comorbidities. Increased knowledge is known through the mother's success in correctly answering the questions given by the resource person.